The development of transformational leadership amongst the Iban community leaders in the three resettlement areas in Kanowit District, Sarawak - Aris, Anak Alap (1998)
The primary purpose of this study was to explore the emergence of Transformational Leadership amongst the Iban community leaders in the three Resettlement Areas in Kanowit District. The respondents were comprised of 57 Community Leaders from the study areas. The demographic characteristics chosen for the purpose of this study were: gender, age, number of years attended school, level of education, income, position, experience as leaders, previous leadership position, how they become leaders, institutionalized visit, official visit, and number of family members working as government servants as independent variables.